(untitled) (Al-Academy, 2024)
The curriculum is a tool of the basic tools that seek through which educational institutions to achieve the objectives of any educational policy, and therefore must be a practical application of curriculum objectives of this policy. If, however, described the separate curricula for educational policy, that would be evidence of planning that leads to failure in achieving the great goals of society. The curriculum does not include the subject of education only, but goes to all the educational experiences that achieve the desired behavioral goals.When goal-setting study for any of the articles should study the use of the overall goals of the article. And therefore must serve the general goals of academic material and objectives in one direction and be consistent with each other and thus working teachers all agreed that their students achieve those goals, the Article (The educators said that all the curriculum should have clear targets and specific, whether the curriculum syllabus or unit) (1). The Teacher basics of the design as a atrainer for the student by the knowledge of all aspects of the teaching of art, because the article did not based on the teaching of this article only. But is active in other materials and to other aspects of the subjects in the scientific section. If the teacher is therefore necessary material foundations of design, it applies to many teachers because it has special meaning for the teacher of art and design as the teacher to understand that assisted teachers in cooperation with other scientific articles in the section all and strengthens the Relation between him and them to benefit from the expertise and experience.Therefore, the current research is trying to take a closer look on the basis of vocabulary curriculum material design. The first chapter was the definition of the importance of research and the need for it and the research problem after putting the following objectives.1. Identified on the vocabulary of the curriculum of the material in terms of the basics of the design (objectives, content).2. Diagnosis of the positive and negative aspects of the curriculum of the basics of the design rule of the Institute. 3. Determine the basic criteria (proposals and solutions) to develop the curriculum of the basics of the design rule of the Institute of Applied Arts, part of the technical education. The boundaries of current research are limited to.1. Reduction objective: limited to items of the curriculum of the basics of the design rule of the Institute of Applied Arts, part of the technical education.2. Reduce spatial: Departments of the Institute of Applied Arts (Interior Design, design and architectural adornment, design layout, design and tailoring) of the Technical Education Commission - Baghdad.3. Temporal limitation: Vocabulary assessments and that continues to work out for the academic year (from 2009 to 2010). The second chapter contains the search procedures through the presentation of the research methodology and procedures. And choose the research community and has appointed it. And actions taken in the preparation of search tool in the collection of information. And then make sure the veracity of the search tool and stability. And several application tool has been applied appropriate statistical methods to get the best results.Chapter III contains the results of research and the conclusions and recommend.dations, proposals and Arabic and foreign sources as well as a summary in Arabic and a summary in English.